FMRP silencing via siRNA lipid nanoparticles to reprogram the tumor microenvironment and enhance anti-PD-1 efficacy in triple-negative breast cancer - Letian Bai; Xinyan Hao; Wenjie Xu; Hai Huang; Mengen Guo; Yanwen Zhang; Daxiong Xiang; Guoping Yang; Junyong Wu; Chuanpin Chen (Materials Today Bio, 2025)
Fragile X mental retardation protein (FMRP), encoded by the Fmr1 gene, is notably upregulated in various malignancies, including triple-negative breast cancer, pancreatic ductal adenocarcinoma, and colon carcinoma, and potentially mediates immune evasion through multiple mechanisms. Here a small interfering RNA (siRNA) targeting Fmr1 is designed for tumor site delivery to suppress FMRP expression and enhance immune activation. Lipid nanoparticles loaded with siFmr1 (LNP@siFmr1) are prepared using a microfluidic-based electrospray method, achieving optimal particle size, encapsulation efficiency, and stability. In an orthotopic breast cancer mouse model, LNP@siFmr1 demonstrates effective passive targeting of tumor sites, leading to significant downregulation of FMRP expression. This suppression coincides with the recruitment and activation of CD8+ T cells and immunostimulatory macrophages, effectively inhibiting tumor growth. Furthermore, the combination with PD-1 antibodies achieves approximately 80 % suppression of tumor growth. These findings provide new insights into tumor-targeted siRNA delivery and immunotherapy strategies involving FMRP targeting and PD-1 antibodies.